Analyzing Madrasah Teacher Performance Assessment in Underdeveloped Areas: A Phenomenological Study in Maluku Province - Eko Wahyunanto Prihono; Wisnu Budi Waluyo; Fitria Lapele; Heri Retnawati; Caly Setiawan (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
Teacher performance assessment is a system designed to determine teachers' capacity to perform their duties by assessing the competence of skills demonstrated in their performance. Analyzing the madrasah teacher' performance assessment in underdeveloped areas of Indonesia is challenging. This study aimed to decipher the experience of assessing the performance of madrasah teachers in underdeveloped regions of Indonesia. It was a qualitative study with a phenomenological approach conducted in Maluku Province. Purposive sampling was used to select samples, including the head of the Islamic Education Department of the Ministry of Religious Affairs of the Regency, the madrasah principals, and teachers assessed for their performance. The data was gathered through interviews and analyzed using an interactive model. The findings revealed five significant problems with the madrasah teacher performances in underdeveloped areas: compliance with teacher performance assessment (TPA) guidelines, implementation, natural conditions, costs, and transportation.